Periodontopathogens, Candida spp. and immunological aspects in type 2 diabetes mellitus patients with chronic periodontitis - Camargo, Gabriela Alessandra da Cruz Galhardo; Silva, Natalia Linhares Coutinho; de Miranda, Ana Luísa Palhares; Tributino, Jorge Luiz Mendonça; Colombo, Natália Helena [UNESP]; Duque, Cristiane [UNESP] (Universidade Estadual de Campinas, 2016)
This study aimed to evaluate clinical, microbiological and immunological parameters in type 2 diabetes mellitus (DM) in comparison with normoglycemic patients (NDM). Glycemic and lipid profiles and periodontal clinical status were determined for thirty-three patients (17 DM and 16 NDM). The presence of periodontopathogens and species of Candida in subgingival sites were determined by polymerase chain reaction and immunological parameters by ELISA assays. All glycemic and clinical parameters evaluated were higher in the DM group, with statistical difference for fasting glucose, glycated-hemoglobin, and periodontal parameters. Lipid profile (except triglycerides), levels of TNF-α and myeloperoxidase and the prevalence of the tested microorganisms were similar between the groups, except for Candida albicans and Candida glabrata, which was higher in the DM group. In conclusion, although microbiological and immunological parameters were similar in the DM and NDM groups, periodontitis and the levels of some species of Candida were more severe in DM patients.
Keywords: Candida spp.; Diabetes mellitus; Myeloperoxidase; Periodontal disease; TNF-α